2010
DOI: 10.1149/1.3484686
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in TOYOTA FCHV-adv Fuel Cell System

Abstract: Toward the mass introduction start in 2015, Toyota continues efforts to overcome the remaining technical challenges for the commercialization of the TOYOTA FCHV. The cold start capability is one of the main issues among such challenges. An excess amount of water in fuel cells hinders the cold start, because the water turns into ice. On the other hand, when there is a lack of water in fuel cells, the initial FC output decreases. To resolve the issue of the cold start capability, the AC impedance measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 10 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…1,2 However, several improvements regarding degradation, performance, and cold start capability have to be achieved to ensure a reliable and durable operation even under extreme ambient operating conditions. 3 The cold start capability of fuel cells has been widely studied on lab-scale [4][5][6][7] as well as on technical fuel cells. 8,9 It has been reported that water does not deposit as ice inside fuel cells; it is produced in its supercooled aggregate state 4,5,7,10 and the phase transition to ice occurs randomly.…”
mentioning
confidence: 99%
“…1,2 However, several improvements regarding degradation, performance, and cold start capability have to be achieved to ensure a reliable and durable operation even under extreme ambient operating conditions. 3 The cold start capability of fuel cells has been widely studied on lab-scale [4][5][6][7] as well as on technical fuel cells. 8,9 It has been reported that water does not deposit as ice inside fuel cells; it is produced in its supercooled aggregate state 4,5,7,10 and the phase transition to ice occurs randomly.…”
mentioning
confidence: 99%
“…Within the last decade, polymer electrolyte fuel cells (PEFCs) have proven their potential to replace fossil fuel based power generators for stationary as well as mobile applications. However, operation under ambient environment 1,2 requires various enhancements regarding degradation, efficiency as well as cold start capability at subfreezing temperatures, where product water risks to freeze. Subzero cold start investigations have been widely reported.…”
mentioning
confidence: 99%
“…As the membrane can initially absorb the water produced, thus avoiding ice formation and performance drop (8,9). The dry gas purge methods have been extensively studied in the literature (10)(11)(12)(13), reducing the degradation due to F/T cycles. However, there are still unsolved issues, especially at extreme low temperatures (e.g.…”
Section: Introductionmentioning
confidence: 99%